A copper(i) bromide organic–inorganic zwitterionic coordination compound with a new type of core: structure, luminescence properties, and DFT calculations. (3rd June 2020) - Berezin, Alexey S.; Artem'ev, Alexander V.; Komarov, Vladislav Y.; Baranov, Andrey Y.
Abstract : A new organic–inorganic Cu(i ) bromide complex based on protonated tris(2-pyridyl)phosphine, [(HPy)3 PCu2 Br5 ], has been synthesized by a straightforward reaction in solution or by modification of the [Cu2 Br2 (Py3 P)2 ] complex using hydrobromic acid. Abstract : A new organic–inorganic Cu(i ) bromide complex based on triple protonated tris(2-pyridyl)phosphine (HPy)3 P, [(HPy)3 PCu2 Br5 ] (1 ), has been synthesized by a straightforward reaction in solution or by modification of the [Cu2 Br2 (Py3 P)2 ] complex using hydrobromic acid. At 77 K, the solid complex 1 exhibits near infra-red photoluminescence with λ max = 680 nm related to 3 (M + X)LCT. The emission of 1 rapidly decreases with increasing temperature and is absent at 200 K due to thermal quenching with a small energy barrier Δ E ≈ 590 cm −1 . The photophysical results are in good agreement with the TD-DFT calculations showing that in the ground state the cuprophilic interaction between copper ions is absent in spite of the short Cu⋯Cu distance. After annealing of complex 1 at 120 °C, photoluminescence occurred with λ max = 640 nm at 300 K. Complex 1 exhibits a luminescence response in ammonia gas consisting of the appearance of luminescence with λ max = 520 nm followed by the gradual enhancement of the luminescence intensity.